2017
DOI: 10.3153/jfhs17017
|View full text |Cite
|
Sign up to set email alerts
|

The Assesment of Relation Between Waist/Height Ratio and Type 2 Diabetes Risk Among Nursing Students

Abstract: Öz:Bu araştırmada hemşirelik bölümü öğrencilerinin tip 2 diyabet riski ile bel/boy oranı ve tip 2 diyabet riski iliş-kisinin değerlendirilmesi amaçlanmıştır. Vücut ağırlığı, boy uzunluğu, bel ve kalça çevresi ölçümleri tekniğine uygun olarak yapılmış ve Finlandiya tip 2 diyabet riski anketi uygulanmıştır. Öğrencilerin %67.1'inin 10 yıllık tip 2 diyabet riskinin %1, %28.5'inin 10 yıllık diyabet riskinin %4, %2.2'sinin 10 yıllık tip 2 diyabet riskinin %16 ve %2.2'sinin 10 yıllık tip 2 diyabet riskinin %33 olduğu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
2
5
1
3
Order By: Relevance
“…Additionally, 61.7% of the males and 65.4% of the females were classified as low risk. The data obtained showed results similar to studies conducted with university students in Northern Cyprus by Gezer, 31 in Turkey by Demirağ et al 28 and Çolak, 32 in Jordan by Al‐Shudifat et al, 33 in the United States by Hamman et al, 7 and in Poland by Morawiec et al 29 However, although the majority of male and female students were classified in the low‐risk group in the present study, both females and males demonstrated low consumption of fruit and vegetables. Nurses should promote healthy food consumption in young adults, because an unhealthy diet is likely to increase the risk of obesity and T2DM in the long term.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, 61.7% of the males and 65.4% of the females were classified as low risk. The data obtained showed results similar to studies conducted with university students in Northern Cyprus by Gezer, 31 in Turkey by Demirağ et al 28 and Çolak, 32 in Jordan by Al‐Shudifat et al, 33 in the United States by Hamman et al, 7 and in Poland by Morawiec et al 29 However, although the majority of male and female students were classified in the low‐risk group in the present study, both females and males demonstrated low consumption of fruit and vegetables. Nurses should promote healthy food consumption in young adults, because an unhealthy diet is likely to increase the risk of obesity and T2DM in the long term.…”
Section: Discussionsupporting
confidence: 86%
“…Yapılan diğer benzer çalışma bulguları da üniversite öğrencilerinin normal kiloda olduğunu, obezite görülme oranının oldukça düşük olduğunu göstermektedir. (17,18,(24)(25)(26)(27) Üniversite öğrencileri ile yürütülen benzer çalışmalarda, fazla kilo görülme sıklığının ise %8.5-%20 arasında değişebildiği; (22,26,28) kadın öğrencilerde obezite görülme sıklığının erkeklere kıyasla daha yüksek olduğu belirtilmektedir. (29)(30)(31) Obezitenin herhangi bir yaşta başlayabilmesine karşın, (32) kilo fazlalığı ve obezite görülme sıklığının hem erkeklerde hem de kadınlarda yaş ile arttığı bilinmektedir.…”
Section: Discussionunclassified
“…(21) Çalışmada, BÇ ortalaması 74.41±9.06 cm olarak bulunmuştur. Çetinkaya'nın (17) çalışmasında, üniversite öğrencilerinde BÇ ortalaması 77.94±11.48 cm, benzer şeklide Gezer'in (24) çalışmasında, 76.0±11.4 cm, Yıldırım ve ark. (18) çalışmasında, kadınların BÇ ortalaması 78.33 cm, erkeklerin ise 86.10 cm bulunmuştur.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The increase in the prevalence of type 2 diabetes reaches up to 80% in low-and middle-income countries (1)(2)(3). The Turkish Diabetes Epidemiology (TURDEP-2) study showed that the prevalence of diabetes in Turkey increased from 7.2% to 13.7% (3,5,6). Diabetes develops as a result of several factors including genetic, environmental and lifestyle-related changes (3,7).…”
Section: Introductionmentioning
confidence: 99%